Acute Profound Thrombocytopenia Induced by Eptifibatide Causing Diffuse Alveolar Hemorrhage. (16th July 2021) - Byrd, Gregory; Custovic, Sabina; Byrd, David; Ingrassia Miano, Deanna; Bathla, Jasdeep; Attallah, Antonious
Abstract : Background . Eptifibatide is a glycoprotein IIb/IIIa (GP IIb/IIIa) receptor inhibitor which prevents platelet activation. The mechanism in which eptifibatide causes profound thrombocytopenia is poorly understood. One hypothesis suggests antibody-dependent pathways which cause thrombocytopenia upon subsequent reexposure to eptifibatide. This case reports acute profound thrombocytopenia (platelets < 20 × 10 3 / m m 3 ) within 24 hours of administration. Alveolar hemorrhage occurred during a second eptifibatide infusion 5 days after initial asymptomatic eptifibatide treatment. Case Presentation . A 50-year-old male presenting with a STEMI was treated with eptifibatide during cardiac catheterization. Twelve hours posttreatment, the patient encountered profound thrombocytopenia and hemoptysis. The patient was briefly intubated for airway protection. The patient was stabilized after receiving platelet transfusion and fully recovered. Conclusion . This is one of several cases reported on eptifibatide causing acute profound thrombocytopenia and subsequent alveolar hemorrhage. This case supports the theory in which antibodies contribute to eptifibatide-induced thrombocytopenia.